What Do Israeli University Students Know About Canada? - Glass, Joseph B. (Canadian Jewish Studies / Études juives canadiennes, 2002)
Between March 1996 and October 2000, six groups of studentsin a second- and third-year, optional, semester course in theDepartment of Geography at the Hebrew University ofJerusalem, were asked to complete a general knowledgequestionnaire about Canada. The questions examine the respondents’ knowledge of Canadian geography, culture and society,population, and economic indicators. Analysis of the questionnairesfound that compared with American students living “nextdoor” to Canada, the level of Israeli university students’ knowledgeabout that country is quite high. Israelis know more aboutCanadian geography, sports, and economics, and about the flagof Canada than about other aspects of life there. They are familiarwith Canadian pop culture figures, although they may notrecognize them as Canadian. Israeli students’ awareness ofCanada is eclipsed by their knowledge of the United States,which occupies a central role in the Israeli consciousness.